2010
DOI: 10.3109/09513591003632209
|View full text |Cite
|
Sign up to set email alerts
|

Relation of body fat distribution to femoral neck bone density and endometrial thickness in postmenopausal women

Abstract: Truncal adiposity rather than overall adiposity or lean mass are more closely associated with femoral neck BMD and there is no relationship between subcutaneous fat mass and endometrial thickness in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…A few previous study reported that ultrasonographic EMT shows a positive correlation with BMD in postmenopausal women consistent with our results. 20 , 21 Considering mean age and proportion of postmenopausal status of this present study (52.1 ± 8.5 and 63.4%), this result was consistent with the previous studies with subjects of similar age. 22 , 23 Unlike these studies which showed this correlation with healthy postmenopausal women, this present study was conducted with breast cancer survivors.…”
Section: Discussionsupporting
confidence: 93%
“…A few previous study reported that ultrasonographic EMT shows a positive correlation with BMD in postmenopausal women consistent with our results. 20 , 21 Considering mean age and proportion of postmenopausal status of this present study (52.1 ± 8.5 and 63.4%), this result was consistent with the previous studies with subjects of similar age. 22 , 23 Unlike these studies which showed this correlation with healthy postmenopausal women, this present study was conducted with breast cancer survivors.…”
Section: Discussionsupporting
confidence: 93%
“…Warming et al [5], studied the body fat distributions of 531 healthy postmenopausal women using dual energy x-ray absorptiometry and found that visceral fat tissue was the primary factor in the production of estrone via the conversion of androgen precursors, arguing it to be the most effective fat tissue on endometrial thickness. Subsequent studies also support the notion that subcutaneous and visceral fat tissues have separate endocrinological functions [11]. Body fat distribution affects the plasma levels of sex hormones.…”
Section: Discussionmentioning
confidence: 66%
“…When an endometrial thickness of 5 mm is accepted as a cutoff value for endometrial pathology in the post-menopausal period, endometrial cancers and atypical endometrial hyperplasias can be detected with a sensitivity of 80.5% and a specifi city of 86.2% [10]. Currently, the literature includes certain studies that suggest a correlation between body fat distribution and ET, yet the role of the former in the determination of an ET greater than 5 mm remains unclear [5,7,11].…”
Section: Introductionmentioning
confidence: 99%